Deregulated microRNAs in CD4+ T cells from individuals with latent tuberculosis versus active tuberculosis. Issue 3 (25th December 2013) - Fu, Yurong; Yi, Zhengjun; Li, Jianhua; Li, Ruifang
Abstract The mechanisms of latent tuberculosis (TB) infection remain elusive. Roles of microRNA (miRNA) have been highlighted in pathogen–host interactions recently. To identify miRNAs involved in the immune response to TB, expression profiles of miRNAs in CD4+ T cells from patients with latent TB, active TB and healthy controls were investigated by microarray assay and validated by RT‐qPCR. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were used to analyse the significant functions and involvement in signalling pathways of the differentially expressed miRNAs. To identify potential target genes for miR‐29, interferon‐γ (IFN‐γ) mRNA expression was measured by RT‐qPCR. Our results showed that 27 miRNAs were deregulated among the three groups. RT‐qPCR results were generally consistent with the microarray data. We observed an inverse correlation between miR‐29 level and IFN‐γ mRNA expression in CD4+ T cells. GO and KEGG pathway analysis showed that the possible target genes of deregulated miRNAs were significantly enriched in mitogen‐activated protein kinase signalling pathway, focal adhesion and extracellular matrix receptor interaction, which might be involved in the transition from latent to active TB. In all, for the first time, our study revealed that some miRNAs in CD4+ T cells were altered in latent and active TB. Function and pathway analysis highlighted the possible involvement of miRNA‐deregulated mRNAs in TB. The study might help to improve understanding of the relationship between miRNAs in CD4+ T cells and TB, and laid an important foundation for further identification of the underlying mechanisms of latent TB infection and its reactivation.